Taxonomic corrections for East and Southeast Asian Reduviidae (Hemiptera: Heteroptera) - Chen, Ling; Wang, Yang; Rédei, Dávid (Zootaxa, 2021)
The identities of certain East and Southeast Asian genera and species of Reduviidae (Hemiptera: Heteroptera) are clarified based on their type materials and taxonomic conclusions are drawn. The following new subjective synonymies and new combinations are proposed: Harpactorinae: Cutocoris Stål, 1859 = Paracydnocoris Miller, 1954, syn. nov.; Cutocoris distinctus (Miller, 1954), comb. nov. (transferred from Paracydnocoris) = Cydnocoris ventralis Hsiao, 1979, syn. nov.; Cutocoris macgillavryi (Miller, 1954), comb. nov. (transferred from Paracydnocoris); Henricohahnia wangi Ren, 2001 = H. obscara Cai & Li, 2003, syn. nov.; Pahabengkakia Miller, 1941 = Stalireduvius Tomokuni & Cai, 2004, syn. nov.; Pahabengkakia piliceps Miller, 1941 = S. nodipes Tomokuni & Cai, 2004, syn. nov.; Reduviinae: Reduvius xantusi (Horváth, 1879), comb. nov. (transferred from Velitra) = R. decliviceps Hsiao, 1976, syn. nov. Pahabengkakia piliceps is recorded from Laos for the first time.